The Correlation between Diction and Scheme Mastery with Students' Reading Comprehension at The Fifth Grade Students - Muhammad Rodi; Dian Permanasari; Febriyanti Febriyanti (IJLHE: International Journal of Language, Humanities, and Education, 2019)
This study aimed to identify and describe the relationship level of diction and schemata mastery with reading ability at the fifth-grade students of SD Negeri 2 Srikuncoro, Semaka District, in the 2018/2019. This study is a quantitative descriptive method of because the score. The variables in this study are in the form of numbers and are presented in the form of tabulation and using statistical analysis. The population of this research is students of the fifth grade of SD Negeri 2 Srikuncoro Semaka District Tanggamus District. Semaka 2018/2019 Academic Year consists of 2 classes. Research result shows that the correlation coefficient between diction mastery and reading comprehension ability of 0.776. The correlation coefficient between schemata on the ability to read comprehension of 0.820, while the double coefficient correlation between diction and schemata mastery on the ability to read comprehension of 0.836. The conclusion can be drawn is that there is a very close and significant relationship between vocabulary mastery and schemata with reading comprehension ability in the fifth grade of SD Negeri 2 Srikuncoro, Semaka Tanggamus District, 2018/2019 academic year. This indicates that the better the mastery of diction and schemata owned, the better the reading comprehension ability.